PENGARUH BIAYA TANGGUNG JAWAB SOSIAL TERHADAP KINERJA PERUSAHAAN STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Achmad Fauzi Arifanto (Jurnal Akuntansi dan Ekonomi Bisnis PSDKU kediri, 2012)
ABSTRACT The purpose of this research is to test the effect of CSR on firm financial. This research is motivated by the fact that there is a lower level of activities of CSR and its disclosure and also mixed results from previous research. This research used Corporate Social Disclosure Index (CSDI) as a measure of CSR disclosure, based on indicators from Global Reporting Initiatives (GRI). The samples of this research are 170 public firms listed in Indonesian Stock Exchange (IDX) year 2007 and 2008 Relatively lower score of CSDI shows that CSR disclosure in firms annual report is still low. This may due to there is still no mandatory rules regarding CSR disclosure in Indonesia and the lack of firms awareness of the importance of CSR and its disclosure in annual report. Test results show that CSR disclosure have positive and not significant effect on Return on Equity as a measure of financial performance.